2012
DOI: 10.1039/c2mb25070e
|View full text |Cite
|
Sign up to set email alerts
|

Upregulated MALAT-1 contributes to bladder cancer cell migration by inducing epithelial-to-mesenchymal transition

Abstract: Recent studies reveal that long non-coding RNAs (lncRNAs) have been shown to have important regulatory roles in cancer biology, and lncRNA MALAT-1 expression is upregulated in some tumors. However, the contributions of MALAT-1 to bladder cancer metastasis remain largely unknown. In the present study we evaluated MALAT-1 expression in bladder cancer tissues by real-time PCR, and defined its biological functions. We verified that MALAT-1 levels were upregulated in bladder cancer tissues compared with adjacent no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
237
1
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 314 publications
(246 citation statements)
references
References 30 publications
6
237
1
2
Order By: Relevance
“…9 In this review, we related that some lncRNAs, such as MALAT1 and H19, were found to promote EMT by activating the Wnt/b-catenin pathway in bladder cancer cells. 49,53 A recent study has identified the role of HOTAIR within the context of EMT and has suggested that HOTAIR inhibition could reverse the EMT process in gastric carcinoma cells. Furthermore, the expression of Snail, one of the major transcription factors regulating EMT, could be induced by HOTAIR overexpression, implying that HOTAIR could act as a potential regulator of EMT.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…9 In this review, we related that some lncRNAs, such as MALAT1 and H19, were found to promote EMT by activating the Wnt/b-catenin pathway in bladder cancer cells. 49,53 A recent study has identified the role of HOTAIR within the context of EMT and has suggested that HOTAIR inhibition could reverse the EMT process in gastric carcinoma cells. Furthermore, the expression of Snail, one of the major transcription factors regulating EMT, could be induced by HOTAIR overexpression, implying that HOTAIR could act as a potential regulator of EMT.…”
Section: Discussionmentioning
confidence: 99%
“…However, another report has suggested that MALAT1 promotes EMT by activating the Wnt/bcatenin pathway in bladder cancer cells: the downregulation of MALAT1 resulted in a decrease in the levels of Slug, as well as ZEB1 and ZEB2 (known as transcriptional repressors of E-cadherin), and an increase in CDH1 levels, indicating that MALAT1 promotes EMT by activating Wnt signaling. 49 LncRNA H19 may be involved in a similar regulatory mechanism. H19, an imprinted and maternally expressed oncofetal gene, is located on chromosome 11p15.5 near the IGF II (encoding insulin-like growth factor II) locus.…”
Section: Malat1 H19 and Ccat2-wnt/b-catenin Pathwaymentioning
confidence: 99%
See 1 more Smart Citation
“…According to statistics, human bladder cancer is the fourth leading cause of malignancy in men and currently the tenth most malignant tumor in women (1). According to its pathological features, bladder cancer can be divided into two major groups: urothelial carcinoma (UC) and invasive bladder cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Ying et al [43] found that MALAT-1 levels were up-regulated in bladder cancer tissues compared with adjacent normal tissues, and siRNA-mediated MALAT-1 silencing resulted in a decrease of ZEB1, ZEB2 and Slug levels, and an increase of E-cadherin levels. MALAT-1 promoted EMT by activating Wnt signaling in vitro.…”
Section: Lncrnas In Cancermentioning
confidence: 99%